2019
DOI: 10.25046/aj040549
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Bee Colony-Optimized LSTM for Bitcoin Price Prediction

Abstract: In recent years, deep learning has been widely used for time series prediction. Deep learning model that is most often used for time series prediction is LSTM. LSTM is widely used because of its excellence in remembering very long sequences. However, doing training on models that use LSTM requires a long time. Trying from one model to another model that use LSTM will take a very long time, thus a method is needed for optimizing hyperparameter to get a model with a small RMSE. This research proposed Artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Hence, an optimized LSTM with ABC to forecast the bitcoin price was introduced in Yuliyono and Girsang. 22 The combination of ABC and RNN was also proposed in Bosire 23 for traffic volume forecasting. This time the results were compared with standard backpropagation models.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, an optimized LSTM with ABC to forecast the bitcoin price was introduced in Yuliyono and Girsang. 22 The combination of ABC and RNN was also proposed in Bosire 23 for traffic volume forecasting. This time the results were compared with standard backpropagation models.…”
Section: Related Workmentioning
confidence: 99%
“…In [28], the authors proposed the artificial bee colony (ABC) algorithm, which imitates the behavior of bee colonies in foraging to search for the optimal values of the hyperparameters of the LSTM topology for bitcoin price prediction. The finding of this study showed that the LSTM model evolved using the ABC outperformed handcrafted LSTM models.…”
Section: Related Workmentioning
confidence: 99%
“…The PSO has also been improved by [63] with the Adaptive Cooperative Particle Swarm Optimisation (ACPSO) proposed, which incorporates a learning automata to adaptively split the sub-population of cooperative PSO, thereby making the decision variables with strong coupling connection to enter the same sub-population. Conversely, other SI based optimisers explored for DL include the salp-swarm optimiser [64], harmony search optimiser on variational stacked autoencoders [65], whale optimisation algorithm(WOA) using bidirectional RNN [66], the Artificial Bee Colony (ABC) for optimizing hyperparameters for LSTM models [67], the AC-Parametric WOA (ACP-WOA) [68] for predicting biomedical images, symbiotic organisms search (SOS) algorithm [69], lion swarm optimiser(LSO) [70], and many others. Nevertheless, a comparison of the performance of these genetic algorithms shows that the GWO convergence rate is fastest compared to the Genetic Algorithm (GA), and PSO [71].…”
Section: Particle Swarm Optimisers (Pso)mentioning
confidence: 99%